2021
DOI: 10.3390/biom11050767
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Epigallocatechin-3-gallate (EGCG) Targeting Protein Misfolding in Drug Discovery for Neurodegenerative Diseases

Abstract: The potential to treat neurodegenerative diseases (NDs) of the major bioactive compound of green tea, epigallocatechin-3-gallate (EGCG), is well documented. Numerous findings now suggest that EGCG targets protein misfolding and aggregation, a common cause and pathological mechanism in many NDs. Several studies have shown that EGCG interacts with misfolded proteins such as amyloid beta-peptide (Aβ), linked to Alzheimer’s disease (AD), and α-synuclein, linked to Parkinson’s disease (PD). To date, NDs constitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 247 publications
0
31
0
Order By: Relevance
“…Brazilin had a strong inhibitory effect on the aggregation of Aβ, remodeling Aβ amyloid fibrils by interaction with Aβ 17–42 pentamer [22] . In the past few decades, a subset of phenolic compounds, especially the polyphenols such as curcumin, myricetin, epigallocatechin gallate, hydroxycinnamic acids, rosmarinic acid, and ferulic acid, were reported to have strong anti‐aggregation effects on α‐Syn [26–36] . Interestingly, some compounds containing only one aromatic ring can inhibit α‐Syn aggregation [37] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazilin had a strong inhibitory effect on the aggregation of Aβ, remodeling Aβ amyloid fibrils by interaction with Aβ 17–42 pentamer [22] . In the past few decades, a subset of phenolic compounds, especially the polyphenols such as curcumin, myricetin, epigallocatechin gallate, hydroxycinnamic acids, rosmarinic acid, and ferulic acid, were reported to have strong anti‐aggregation effects on α‐Syn [26–36] . Interestingly, some compounds containing only one aromatic ring can inhibit α‐Syn aggregation [37] .…”
Section: Introductionmentioning
confidence: 99%
“…[22] In the past few decades, a subset of phenolic compounds, especially the polyphenols such as curcumin, myricetin, epigallocatechin gallate, hydroxycinnamic acids, rosmarinic acid, and ferulic acid, were reported to have strong anti-aggregation effects on α-Syn. [26][27][28][29][30][31][32][33][34][35][36] Interestingly, some compounds containing only one aromatic ring can inhibit α-Syn aggregation. [37] Due to the lack of structural information, the detailed mechanisms of α-Syn-phenolic compounds' interactions remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the role of green tea catechins in neuroprotection, with epigallocatechin gallate (EGCG) being widely studied because it constitutes 65% of all catechins in green tea [ 8 , 9 , 10 , 11 ]. The green tea catechins play a variety of roles in neuroprotection, such as exerting (i) anti-oxidative properties through radical scavenging and metal ion chelation [ 12 , 13 , 14 ], (ii) anti-apoptotic properties through the reduction in pro-apoptotic gene expression [ 15 ], (iii) anti-inflammatory properties through the inhibition of microglia activation [ 16 ], and (iv) anti-amyloidogenic properties through the remodeling of toxic aggregates [ 8 , 17 ]. The latter role of catechins in neuroprotection is of great interest as it counteracts the hallmark of NDs (formation of protein aggregates), which is thought to drive the process of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Some aggregated species might be neurotoxic and lead to neurodegeneration [67]. For this reason, targeting neuronal accumulation of α-synuclein is appealing as a promising approach to delaying the progression of AD [68,69].…”
Section: α-Synuclein Inhibitionmentioning
confidence: 99%